Preparing for the Future of Grid-Code - Clifford, Diane; Böhm, Annika (Indian Journal of Power and River Valley Development, 2020)
As growth in distributed energy and other factors increase the risk of instability on electric utility systems, nations and grid providers are tightening grid-code requirements. Developers of distributed energy projects need to stay current with grid-codes and can look to a trusted equipment manufacturer for help with compliance.